A monomer self-polymerization-assisted synthesis perovskite solar cell and its preparation method
By using the monomer self-polymerization strategy in perovskite solar cells to add self-polymerization monomers to perovskite films, the problem of inefficiency of perovskite films in perovskite solar cells is solved, and efficient Photovoltaic performance and stability are enhanced.
Patent Information
- Application Number
- CN202111257778.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-10-27
AI Technical Summary
The existing perovskite solar cells are difficult to accurately control due to the difficulty in controlling the proportion of precursor raw materials, resulting in lead-rich and cesium-rich heterophase products, forming defective states and blocking charge migration. The energy level structure of the perovskite film does not match the charge transport layer. Causes inefficiency.
The monomer self-polymerization strategy is used to add acrylic, acrylate, and acrylamide monomers that are prone to self-polymerization in the aqueous solution of cesium bromide precursor. The ratio of precursor raw materials is accurately controlled through two-step methods to optimize the CsPbBr3 perovskite film Energy level structure reduces defect states, improves the flatness and grain size of the film, and regulates the annealing process of the film through the distribution of polymer chains to optimize interface energy level matching.
The production of perovskite films with high quality and low defect density has been achieved, the photovoltaic performance has been improved, the stability of the device and the tolerance of high humidity environment have been enhanced, and the photoelectric conversion efficiency has been increased to 7.20% to 10.95%.
Smart Images

Figure CN114284441B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy technology and solar cells, and specifically relates to a perovskite solar cell synthesized by using a self-polymerizing monomer as an additive and a preparation method thereof. Background Art
[0002] The perovskite light-absorbing layer is a key part of the perovskite solar cell device. The organic bonding energy between the organic cations and the crystal structure in the organic-inorganic hybrid perovskite material is low and the stability is poor. When the external environment changes, it is very easy to react with water, oxygen, etc. in a highly destructive and irreversible manner, detaching from the original structure and causing the perovskite structure to decompose, seriously reducing the operational stability of the perovskite solar cell. The stability and weather resistance of the all-inorganic perovskite structure are significantly higher, and the assembled battery has stable and good photovoltaic performance. Among them, the all-bromine structure CsPbBr 3 It is a leader among all-inorganic perovskites. It has excellent tolerance to long-term erosion by air, humidity, and continuous light, and is considered to be one of the most promising high-stability light-absorbing materials for perovskite solar cells.
[0003] However, CsPbBr 3 Perovskite solar cells are currently inefficient and still far from their theoretical efficiency. This is mainly due to two reasons. On the one hand, the existing multi-step method for preparing CsPbBr 3 In the perovskite structure, lead-rich and cesium-rich impurity products are prone to appear because the ratio of precursor raw materials cannot be accurately controlled, thus forming defect states and blocking the rapid migration of charges, which can easily cause radiative recombination and non-radiative recombination of carriers inside the device; on the other hand, CsPbBr 3 The mismatch between the energy level structure of perovskite and the charge transport layer results in serious charge recombination and energy loss during charge migration. Recently, a study has proposed that CsPbBr can be prepared by precisely controlling the ratio of precursor raw materials in a two-step method. 3Perovskite film, but this method crystallizes too fast, the surface of the film is not dense and flat, there are a lot of pores, and the grain size is small, so that the density of defect states inside the film is high, the contact with the next electrode interface is also poor, the charge recombination is prominent and the charge extraction efficiency is low, resulting in unsatisfactory photovoltaic performance of the device. Recently, additive engineering has been widely used to regulate the crystallization dynamics of perovskite and the electron arrangement inside the crystal to improve the film quality and optimize the band structure, while passivating the defect states in the perovskite film, thereby promoting carrier extraction and inhibiting charge recombination, and ultimately improving the photovoltaic performance of the battery. Most of the existing additives are organic compounds, which can be divided into small molecule additives and macromolecular additives, but small molecule additives are easily decomposed and lose their function during the high temperature annealing process of perovskite preparation, while macromolecular additives have poor solubility and are difficult to disperse evenly inside the perovskite, and cannot fully play a positive role. They are easy to become the center of charge recombination and induce the formation of defect states. In addition, the residual tensile and compressive stresses are generated during the annealing process of the perovskite film due to the difference in volume expansion and contraction coefficients with the substrate, which distorts the perovskite lattice and causes a large number of defect states that cause non-radiative recombination, reducing the charge extraction and photoelectric conversion efficiency of the device. Therefore, how to use a simple and effective method to prepare a uniform and dense perovskite film with high flatness, high crystallinity, low defect state density, and suitable band structure has become a key topic in the research of perovskite solar cells. Summary of the invention
[0004] The object of the present invention is to provide a perovskite solar cell synthesized by assisting monomer self-polymerization strategy and a preparation method thereof.
[0005] The invention prepares high-quality CsPbBr by adding acrylic acid, acrylic ester, acrylamide and bisacrylamide self-polymerizing monomers to the aqueous solution of cesium bromide precursor, and adopts a two-step method that can accurately control the ratio of precursor raw materials. 3 First, the good solubility of the organic small molecule monomer ensures its dispersibility and uniform binding in the cesium bromide aqueous solution, and the preheating before the reaction causes the monomer to prepolymerize to improve its stability and the viscosity of the cesium bromide solution, which can fully delay the penetration of cesium bromide in the lead bromide film and the crystallization kinetics of the perovskite, reduce the formation of crystal nuclei, and increase the CsPbBr 3The grain size of the film, and the volume shrinkage of the organic small molecule monomers during self-polymerization, can provide space for the volume expansion of the perovskite crystal phase transformation to facilitate the full growth of the crystal, while reducing the compressive stress in the film, reducing the perovskite lattice distortion and the resulting defect states; secondly, these organic small molecule monomers self-polymerize into long-chain polymer chains during the perovskite annealing process, and are orderly distributed in the film. In addition, the electron-donating groups on the polymer chains combine with positively charged ions to uniformly limit the volume expansion and passivation defects during the perovskite annealing process, eliminate the tensile stress and defect states in the film, improve the film quality and surface smoothness, and enhance the interface contact with the next electrode layer; in addition, the addition of monomer self-polymerization products containing different functional groups will rearrange the electron distribution in the perovskite film, thereby adjusting the optical band gap and band structure of the perovskite, optimizing the interface energy level matching between the perovskite layer and the charge transport layer, accelerating charge transfer and inhibiting energy loss. Based on the above monomer self-polymerization-assisted synthesis of perovskite solar cells, the CsPbBr 3 Photovoltaic performance of perovskite solar cells.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0007] The present invention provides a monomer self-polymerization-assisted synthesis perovskite solar cell and a preparation method thereof, which comprises the following steps:
[0008] (1) Spin coating 0.1-1 mol / L isopropyl titanate and 0.03-0.3 mol / L diethanolamine ethanol solution on FTO glass, and sintering at high temperature to obtain a titanium dioxide dense layer; spin coating 0.05-0.1 mol / L titanium dioxide slurry on the titanium dioxide dense layer, and sintering at high temperature to obtain a titanium dioxide mesoporous layer; immersing the obtained titanium dioxide dense / mesoporous layer in 0.01-0.1 mol / L titanium tetrachloride aqueous solution, washing, and sintering at high temperature to obtain a titanium dioxide electron transport layer;
[0009] (2) Prepare a 0.5-1 mol / L lead bromide DMF solution, and prepare a 0.5-2 mol / L cesium bromide aqueous solution to which a self-polymerizing monomer is added; the self-polymerizing monomer is one or more of acrylic acid, acrylic acid ester, acrylamide and bisacrylamide organic substances, and its structural formula is as follows: Figure 1 As shown. Wherein, R1 can be a hydrogen group, an alkyl group, or an amino group; R2 can be a hydrogen group, an alkyl group, an alkenyl group, an alkynyl group, a phenyl group, a naphthyl group, an acyl group, a carboxyl group, an amino group, a hydroxyl group, or a chloro group; R3 and R4 can be a hydrogen group, an alkyl group, an alkenyl group, a phenyl group, a naphthyl group, a benzyl group, or a carboxyl group; and R5 can be an alkyl group;
[0010] (3) spin coating the lead bromide DMF solution on the titanium dioxide electron transport layer, and annealing to obtain a lead bromide thin film;
[0011] (4) Spin-coating the cesium bromide aqueous solution prepared in step (2) on the lead bromide film, and annealing the film by gradient temperature increase to obtain CsPbBr containing the self-polymerization product of the self-polymerization monomer. 3 Perovskite thin films;
[0012] (5) Applying conductive carbon slurry on the perovskite film, heating and curing to obtain a back electrode, and assembling a perovskite solar cell synthesized by monomer self-polymerization.
[0013] Furthermore: in the step (2), the concentration ratio of lead bromide to cesium bromide is 1:1-2.
[0014] Furthermore, the concentration of the self-polymerizing monomer added in step (2) is 0.1-1 mg / mL, the heating temperature for preparing the cesium bromide aqueous solution containing the self-polymerizing monomer is 30-90° C., the stirring speed is 500-1500 rpm, and the stirring time is 2-6 hours.
[0015] Furthermore, before spin coating in step (3), the lead bromide DMF solution is preheated at 70-100° C. for 30-60 minutes, 45-90 μl of the solution is taken for spin coating, the spin coating speed is 1000-3000 rpm, the spin coating time is 30-60 seconds, the annealing temperature is 70-100° C., and the annealing time is 30-60 minutes.
[0016] Furthermore, before spin coating in step (4), the cesium bromide aqueous solution prepared in step (2) and the lead bromide film prepared in step (3) are preheated at 70-100° C. for 30-60 minutes, 50-100 μl of the solution are spin coated at a spin coating speed of 1000-3000 rpm for 30-60 seconds, and then gradient temperature annealing is performed, i.e., annealing is performed at 70-100° C. for 10-30 minutes, then the temperature is increased to 160-250° C., and annealing is performed for 10-30 minutes.
[0017] The present invention also provides a monomer self-polymerization-assisted synthesized perovskite solar cell obtained by the preparation method.
[0018] The perovskite solar cell has an open circuit voltage of 1.25 to 1.65 V and a short circuit current density of 7.01 to 7.76 mA·cm -2 , the filling factor is 0.77~0.85, and the photoelectric conversion efficiency is 7.20%~10.95%.
[0019] The present invention also provides the use of the monomer self-polymerization-assisted synthesized perovskite solar cell as a battery component and in a power station.
[0020] Compared with the prior art, the advantages and technical effects of the present invention are as follows: 1. The present invention adopts a two-step method that can accurately control the ratio of precursor raw materials to prepare CsPbBr 3 Compared with the existing multi-step method, the perovskite film has simple steps and is easy to operate. It can effectively control the purity of the perovskite phase, the morphology and thickness of the film, inhibit the formation of lead-rich and cesium-rich impurity phases, and improve the quality of the film. At the same time, the gradient annealing method can achieve CsPbBr at a lower temperature of 160°C. 3 The preparation of perovskite reduces energy consumption and is conducive to the development of commercial applications. The present invention uses deionized water instead of methanol to prepare the cesium bromide precursor solution, which is green and environmentally friendly and more in line with the concept of sustainable development.
[0021] 2. The present invention adds self-polymerizable small-molecule organic monomers to the cesium bromide precursor solution, which can effectively avoid the problem of polymer precipitation due to excessive molecular weight compared to directly incorporating the polymer into the perovskite layer. In addition, the problem that small organic molecules are difficult to stably exist in the perovskite structure due to their high volatility and disorder is also effectively solved because small monomer molecules will self-polymerize to form polymers during the preparation of perovskite films.
[0022] 3. The present invention utilizes the added small molecule monomer to self-polymerize and shrink in volume, providing space for the volume expansion of perovskite during the crystal transformation process, which is conducive to the uniform growth of perovskite crystals and reduces the compressive stress in the film, increases the grain size of the film, inhibits lattice distortion, and reduces defect states. At the same time, the uniform dispersion and prepolymerization of small molecule monomers in the cesium bromide precursor solution are used to increase the viscosity, fully slow down the penetration of the cesium bromide solution and the crystallization rate of the perovskite, and obtain a perovskite film with a large grain size. In addition, the addition of monomer self-polymers containing electron-donating groups can effectively passivate the positive charge ion state defects in the perovskite film and regulate the tensile stress and band structure of the film, optimize the energy level matching at the interface, increase the carrier migration speed, and inhibit non-radiative and radiative recombination and energy loss in the battery.
[0023] 4. The present invention utilizes monomer self-polymerization to assist the synthesis of CsPbBr 3 The perovskite film has low surface roughness and a small number of grain boundaries, which can form a close and good interface contact with the next layer of carbon electrode and prevent the penetration of water vapor, effectively improving the high humidity environment tolerance of the unpackaged device. 3 After operating for 30 days in a natural environment with a high relative humidity of 85%, the photoelectric conversion efficiency of the perovskite solar cell can still be maintained at more than 95% of the initial value ≥10.20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a structural diagram of the self-polymerizing monomer added in the present invention.
[0025] FIG. 2 is an infrared spectrum of the perovskite synthesized by monomer self-polymerization assisted prepared by the present invention.
[0026] FIG3 is a CsPbBr prepared by the present invention with the aid of monomer self-polymerization. 3 Diagram of the optical band gap of perovskites.
[0027] Figure 4 This is a JV curve diagram of the perovskite solar cell synthesized by monomer self-polymerization assisted by the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods, but is not limited to the embodiments.
[0029] Example 1
[0030] 1. Prepare 0.5 mol / L ethanol solution of isopropyl titanate, prepare 0.1 g / mL titanium dioxide slurry, prepare 0.04 mol / L titanium tetrachloride aqueous solution, prepare 1 mol / L lead bromide DMF solution, prepare 250 mg / mL cesium bromide aqueous solution to which 0.25 mg / mL N-hydroxymethyl acrylamide is added;
[0031] 2. Spin coating 90 μL of the ethanol solution of isopropyl titanate on the FTO conductive glass for 30 seconds (at a speed of 7000 rpm), and calcining at 550°C for 2 hours to obtain a titanium dioxide dense layer; spin coating 90 μL of the titanium dioxide slurry on the titanium dioxide dense layer for 30 seconds (at a speed of 3000 rpm), and calcining at 450°C for 60 minutes to obtain a titanium dioxide mesoporous layer; immersing the titanium dioxide mesoporous layer in the titanium tetrachloride solution for 30 minutes, heating in a water bath at 75°C, washing, and calcining at 450°C for 60 minutes to obtain a titanium dioxide electron transport layer with a thickness of about 200 nm;
[0032] 3. Spin-coat 90 μL of the lead bromide DMF solution preheated at 90° C. for 30 minutes on the titanium dioxide electron transport layer (rotation speed is 2000 rpm) for 30 seconds, and then anneal at 90° C. for 30 minutes to obtain a lead bromide film;
[0033] 4. Spin 90 μl of an aqueous solution of cesium bromide added with N-hydroxymethyl acrylamide preheated at 90°C for 30 minutes on a lead bromide film preheated at 90°C for 30 minutes for 30 seconds (at a speed of 2000 rpm), anneal at 90°C for 10 minutes, then heat to 160°C for 10 minutes to obtain CsPbBr 3 Perovskite film, with a grain size of about 500nm and a thickness of 400nm;
[0034] 5. Apply conductive carbon slurry on the perovskite film, heat at 90° C. for 30 minutes to solidify to obtain a back electrode with a thickness of about 15 μm, and assemble into a perovskite solar cell synthesized by N-hydroxymethyl acrylamide self-polymerization.
[0035] Example 2
[0036] 1. Prepare 0.5 mol / L ethanol solution of isopropyl titanate, prepare 0.1 g / mL titanium dioxide slurry, prepare 0.04 mol / L titanium tetrachloride aqueous solution, prepare 1 mol / L lead bromide DMF solution, prepare 250 mg / mL cesium bromide aqueous solution to which 0.5 mg / mL N-hydroxymethyl acrylamide was added;
[0037] 2. Spin coating 90 μL of the ethanol solution of isopropyl titanate on the FTO conductive glass for 30 seconds (at a speed of 7000 rpm), and calcining at 550°C for 2 hours to obtain a titanium dioxide dense layer; spin coating 90 μL of the titanium dioxide slurry on the titanium dioxide dense layer for 30 seconds (at a speed of 3000 rpm), and calcining at 450°C for 60 minutes to obtain a titanium dioxide mesoporous layer; immersing the titanium dioxide mesoporous layer in the titanium tetrachloride solution for 30 minutes, heating in a water bath at 75°C, washing, and calcining at 450°C for 60 minutes to obtain a titanium dioxide electron transport layer with a thickness of about 200 nm;
[0038] 3. Spin-coat 90 μL of the lead bromide DMF solution preheated at 90° C. for 30 minutes on the titanium dioxide electron transport layer (rotation speed is 2000 rpm) for 30 seconds, and then anneal at 90° C. for 30 minutes to obtain a lead bromide film;
[0039] 4. Spin 90 μl of an aqueous solution of cesium bromide added with N-hydroxymethyl acrylamide preheated at 90°C for 30 minutes on a lead bromide film preheated at 90°C for 30 minutes for 30 seconds (at a speed of 2000 rpm), anneal at 90°C for 10 minutes, then heat to 160°C for 10 minutes to obtain CsPbBr 3 Perovskite film with a grain size of about 600nm and a thickness of 400nm;
[0040] 5. Apply conductive carbon slurry on the perovskite film, heat at 90° C. for 30 minutes to solidify to obtain a back electrode with a thickness of about 15 μm, and assemble into a perovskite solar cell synthesized by N-hydroxymethyl acrylamide self-polymerization.
[0041] Example 3
[0042] 1. Prepare 0.5 mol / L ethanol solution of isopropyl titanate, prepare 0.1 g / mL titanium dioxide slurry, prepare 0.04 mol / L titanium tetrachloride aqueous solution, prepare 1 mol / L lead bromide DMF solution, prepare 250 mg / mL cesium bromide aqueous solution to which 0.75 mg / mL N-hydroxymethyl acrylamide is added;
[0043] 2. Spin coating 90 μL of the ethanol solution of isopropyl titanate on the FTO conductive glass for 30 seconds (at a speed of 7000 rpm), and calcining at 550°C for 2 hours to obtain a titanium dioxide dense layer; spin coating 90 μL of the titanium dioxide slurry on the titanium dioxide dense layer for 30 seconds (at a speed of 3000 rpm), and calcining at 450°C for 60 minutes to obtain a titanium dioxide mesoporous layer; immersing the titanium dioxide mesoporous layer in the titanium tetrachloride solution for 30 minutes, heating in a water bath at 75°C, washing, and calcining at 450°C for 60 minutes to obtain a titanium dioxide electron transport layer with a thickness of about 200 nm;
[0044] 3. Spin-coat 90 μL of the lead bromide DMF solution preheated at 90° C. for 30 minutes on the titanium dioxide electron transport layer (rotation speed is 2000 rpm) for 30 seconds, and then anneal at 90° C. for 30 minutes to obtain a lead bromide film;
[0045] 4. Spin 90 μl of an aqueous solution of cesium bromide added with N-hydroxymethyl acrylamide preheated at 90°C for 30 minutes on a lead bromide film preheated at 90°C for 30 minutes for 30 seconds (at a speed of 2000 rpm), anneal at 90°C for 10 minutes, then heat to 160°C for 10 minutes to obtain CsPbBr 3 Perovskite film with a grain size of about 500nm and a thickness of 400nm;
[0046] 5. Apply conductive carbon slurry on the perovskite film, heat at 90° C. for 30 minutes to solidify to obtain a back electrode with a thickness of about 15 μm, and assemble into a perovskite solar cell synthesized by N-hydroxymethyl acrylamide self-polymerization.
[0047] Comparative Example 1
[0048] 1. Prepare 0.5 mol / L ethanol solution of isopropyl titanate, prepare 0.1 g / mL titanium dioxide slurry, prepare 0.04 mol / L titanium tetrachloride aqueous solution, prepare 1 mol / L lead bromide DMF solution, prepare 250 mg / mL cesium bromide aqueous solution;
[0049] 2. Spin coating 90 μL of the ethanol solution of isopropyl titanate on the FTO conductive glass for 30 seconds (at a speed of 7000 rpm), and calcining at 550°C for 2 hours to obtain a titanium dioxide dense layer; spin coating 90 μL of the titanium dioxide slurry on the titanium dioxide dense layer for 30 seconds (at a speed of 3000 rpm), and calcining at 450°C for 60 minutes to obtain a titanium dioxide mesoporous layer; immersing the titanium dioxide mesoporous layer in the titanium tetrachloride solution for 30 minutes, heating in a water bath at 75°C, washing, and calcining at 450°C for 60 minutes to obtain a titanium dioxide electron transport layer with a thickness of about 200 nm;
[0050] 3. Spin-coat 90 μL of the lead bromide DMF solution preheated at 90° C. for 30 minutes on the titanium dioxide electron transport layer (rotation speed is 2000 rpm) for 30 seconds, and then anneal at 90° C. for 30 minutes to obtain a lead bromide film;
[0051] 4. Preheat 90 μl of the cesium bromide aqueous solution for 30 minutes and then spin coat it on the lead bromide film for 30 seconds (rotation speed is 2000 rpm), anneal at 90°C for 10 minutes and then heat to 160°C for 10 minutes to obtain CsPbBr 3 Perovskite film, with a grain size of about 400nm and a thickness of 300nm;
[0052] 5. Apply conductive carbon slurry on the perovskite film, heat at 90° C. for 30 minutes to solidify to obtain a back electrode with a thickness of about 15 μm, and assemble into an original control perovskite solar cell.
[0053] The photovoltaic performance of the solar cells of the above embodiment and comparative example is shown in the following table:
[0054] <![CDATA[J SC (mA cm -2 )]]> <![CDATA[V OC (V)]]> FF(%) PCE(%) Example 1 7.21 1.38 80.40 8.00 Example 2 7.46 1.43 78.93 8.42 Example 3 7.01 1.34 77.37 7.29 Comparative Example 1 6.79 1.33 74.11 6.69
[0055] By comparing Examples 1, 2, and 3 with Comparative Example 1, it can be seen that adding an appropriate concentration of N-hydroxymethyl acrylamide monomer to the cesium bromide precursor raw material can significantly improve the photovoltaic performance of the prepared perovskite solar cell, and the fill factor, short-circuit current, and open-circuit voltage of the battery are significantly improved. Although adding more N-hydroxymethyl acrylamide monomer will cause the non-conductive polymer formed by self-polymerization to accumulate in the battery, and the self-polymer itself is also a defect state, too high a content will break through the tolerance limit of the perovskite structure, produce a negative impact, and make the photoelectric conversion efficiency of the battery show a trend of first increasing and then decreasing, but they are all higher than the original control device without adding monomers.
[0056] like Figure 2aAs shown, the N-hydroxymethyl acrylamide (HAM) monomer added by the above-mentioned invention method effectively passivates the metal cation defect states in the perovskite, and the HAM monomer is prepolymerized in the cesium bromide precursor raw material, and then further polymerized during the gradient annealing process to prepare the perovskite (such as Figure 2b As shown in FIG3 , the optical band gap of the perovskite film prepared by the above-mentioned inventive method is narrowed, which can increase the absorption spectrum range of the perovskite film. The photovoltaic performance results of the perovskite solar cell prepared in the example are shown in FIG3 . Figure 4 As shown, the open circuit voltage is 1.25~1.65V and the short circuit current density is 7.01~7.76mA·cm -2 , the filling factor is 0.77~0.85, and the photoelectric conversion efficiency is 7.20%~10.95%.
[0057] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing a perovskite solar cell synthesized by monomer self-polymerization, characterized in that The following steps are involved: (1) Spin coating 0.1-1 mol / L isopropyl titanate and 0.03-0.3 mol / L diethanolamine ethanol solution on FTO glass, and sintering at high temperature to obtain a titanium dioxide dense layer; spin coating 0.05-0.1 mol / L titanium dioxide slurry on the titanium dioxide dense layer, and sintering at high temperature to obtain a titanium dioxide mesoporous layer; immersing the obtained titanium dioxide dense / mesoporous layer in 0.01-0.1 mol / L titanium tetrachloride aqueous solution, washing, and sintering at high temperature to obtain a titanium dioxide electron transport layer; (2) Prepare a DMF solution of lead bromide with a concentration of 0.5 to 1 mol / L, and prepare a cesium bromide aqueous solution with a concentration of 0.5 to 2 mol / L to which a self-polymerizing monomer is added; the self-polymerizing monomer is one or more of acrylic acid, acrylic acid ester, acrylamide and bisacrylamide organic substances, and its structural formula is: Wherein, R1 is one or more of hydrogen, alkyl, and amino; R2 is one or more of hydrogen, alkyl, alkenyl, alkynyl, phenyl, naphthyl, acyl, carboxyl, amino, hydroxyl, and chloro; R3 and R4 are one or more of hydrogen, alkyl, alkenyl, phenyl, naphthyl, benzyl, and carboxyl; and R5 is an alkyl; (3) spin coating the lead bromide DMF solution on the titanium dioxide electron transport layer, and annealing to obtain a lead bromide thin film; (4) spin coating the cesium bromide aqueous solution prepared in step (2) on the lead bromide film, and annealing the film at a gradient temperature to obtain a CsPbBr3 perovskite film containing a self-polymerization product of a self-polymerization monomer; (5) Applying conductive carbon slurry on the perovskite film, heating and curing to obtain a back electrode, and assembling a perovskite solar cell synthesized by monomer self-polymerization.
2. The method for preparing a perovskite solar cell synthesized by monomer self-polymerization according to claim 1, characterized in that: In the step (2), the concentration ratio of lead bromide to cesium bromide is 1:1-2.
3. The method for preparing a perovskite solar cell synthesized by monomer self-polymerization according to claim 1, characterized in that: The concentration of the self-polymerizing monomer added in step (2) is 0.1-1 mg / mL, the heating temperature for preparing the cesium bromide aqueous solution added with the self-polymerizing monomer is 30-90° C., the stirring speed is 500-1500 rpm, and the stirring time is 2-6 hours.
4. The method for preparing a perovskite solar cell synthesized by monomer self-polymerization according to claim 1, characterized in that: In the step (3), the lead bromide DMF solution is preheated at 70-100° C. for 30-60 minutes before spin coating, 45-90 μl of the solution is taken for spin coating, the spin coating speed is 1000-3000 rpm, the spin coating time is 30-60 seconds, the annealing temperature is 70-100° C., and the annealing time is 30-60 minutes.
5. The method for preparing a perovskite solar cell synthesized by monomer self-polymerization according to claim 1, characterized in that: Before spin coating in step (4), the cesium bromide aqueous solution prepared in step (2) and the lead bromide film prepared in step (3) are preheated at 70-100° C. for 30-60 minutes, 50-100 μl of the solution are taken for spin coating, the spin coating speed is 1000-3000 rpm, the spin coating time is 30-60 seconds, and then gradient temperature annealing is performed, that is, annealing is first performed at 70-100° C. for 10-30 minutes, then the temperature is increased to 160-250° C., and annealing is performed for 10-30 minutes.
6. A perovskite solar cell synthesized by monomer self-polymerization assisted synthesis obtained by the preparation method according to any one of claims 1 to 5.
7. The monomer self-polymerization-assisted synthesis perovskite solar cell according to claim 6, characterized in that: The perovskite solar cell has an open circuit voltage of 1.25 to 1.65 V and a short circuit current density of 7.01 to 7.76 mA·cm -2 , the filling factor is 0.77~0.85, and the photoelectric conversion efficiency is 7.20%~10.95%.
8. Use of the monomer self-polymerization-assisted synthesized perovskite solar cell as claimed in claim 6 as a battery component and in a power station.
Citation Information
Patent Citations
All-printed mesoscopic perovskite solar cell and preparation method thereof
CN110890466A
Inorganic perovskite solar cell added with CsPbBr3 based on amine compound and preparation method and application thereof
CN111146300A